Jenis Proposisi Dalam Karangan Argumentasi Siswa - Syahruddin Syahruddin; Sumadi Sumadi; Sunaryo Sunaryo (Pascasarjana Universitas Negeri Malang, 2019)
Abstract: This research was aimed to describe the type of proposition on argumentative text of students. This study is a text analysis study. The data of the study was the sentence of students' argumentative text. The data has been analyzed by structural syntactic studies and semantic logic. The result of the study shows that the type of proposition on students' argumentative text are (1) type of proposition based on the source, (2) type of proposition based on the shape, (3) type of proposition based on the character, (4) type of proposition based on the level of certainty of truth, (5) type of proposition based on the quality, (6) type of proposition based on the quantity, and (7) type of proposition based on the combination of quantity and quality. Abstrak: Penelitian ini bertujuan mendeskripsikan jenis proposisi dalam karangan argumentasi siswa. Jenis penelitian ini adalah analisis teks. Data dan sumber data dalam penelitian berupa kalimat-kalimat dalam karangan argumentasi siswa. Data akan dianalisis dengan kajian sintaksis struktural dan logika semantikal. Hasil penelitian ditemukan jenis proposisi dalam karangan argumentasi siswa, meliputi (1) jenis proposisi berdasarkan sumbernya, (2) jenis proposisi berdasarkan bentuknya, (3) jenis proposisi berdasarkan sifatnya, (4) jenis proposisi berdasarkan tingkat kepastian kebenaran (5) jenis proposisi berdasarkan kualitasnya, (6) jenis proposisi berdasarkan kuantitasnya, dan (7) jenis proposisi berdasarkan kombinasi kuantitas dan kualitasnya.